From ‘Micro’ flower to ‘Mega’ fruit - Jutta, Mariam; Zawawi, Abu Hanafiah (University Putra Malaysia, 2012)
Most of us are familiar with the curious yellow blobs of nangka (jack fruit) or chempedak - chewy, delectable layers of flesh surrounding large, no less edible seeds. But asked whether they have seen the flowers of a nangka or cempedak tree most people would answer with a perplexed but firm “no”. Yet, flowers they have - members of the genus Artocarpus to which nangka, cempedak and sukun belong, bear male and female flowers on separate distinct inflorescences on the same tree.